Drug Utilization Pattern and Potential Teratogenicity Risk among Pregnant Women Visiting Antenatal Clinic: The Case of a Primary Hospital - Fikadu, Mesfin; Kebebe, Dereje; Amelo, Wote; Gashe, Fanta (Indian Journal of Pharmacy Practice)
Background: Pregnancy is a special physiological condition where the treatment needs a special concern. Moreover, pharmacotherapy during pregnancy is very challenging since only a few medicines have been specifically tested for safety. Objective: The aim of this study was to evaluate the utilization pattern and the teratogenicity risk of the drugs prescribed to pregnant women in Fiche Hospital, Ethiopia. Methods: A retrospective study was conducted by reviewing medical case files of 323 pregnant women, encountered with at least one drug, out of 1876 pregnant women attending antenatal clinic from February 09/2013 to March 09/2014. The prescription pattern was assessed from perspectives of World Health Organization (WHO) core drug use indicators, and the United States Food and Drug Administration (FDA) fetal harm classification. Results: Among 1876 pregnant women who visited ANC clinic, a total of 323 women received 456 medications. The age of the patients was within the range of 16-49 years and the majority of them (77.22%) were within the age group of 20-35 years. The majority of pregnant women (80.47%) visited antenatal care (ANC) during their first trimester gestation. Out of the total drugs prescribed, category A drugs comprised 20.83%, category B (26.34%), category C (24.34%), category C/D (9.65%), category D (9.43%) and category X (1.09%). Percentage of encounter with antibiotics and injectable drugs were 31.8% and 19.30%, respectively. Conclusion: Approximately half of the pregnant women utilized drugs from FDA category C, D and X which are thought to cause fetal harm; therefore, the use of these drugs should be minimized.
Keywords: FDA drug category; Pregnancy; Teratogen; Trimester; WHO core drug prescribing indicators